2010
DOI: 10.1007/s10856-010-3993-9
|View full text |Cite
|
Sign up to set email alerts
|

Transfection efficiency of depolymerized chitosan and epidermal growth factor conjugated to chitosan–DNA polyplexes

Abstract: An efficient non-viral gene delivery for varieties of cells has been considered essential for gene therapy and tissue engineering. This study evaluated transfection efficiency of chitosan (HW) with molecular weights (Mw) at 470 and degree of deacetylation (DDA) 80% and its depolymerization product (LW) with Mw at 16 kDa and DDA 54%, as well as epidermal growth factor (EGF) conjugated to chitosan-DNA microparticles of both HW and LW by using either disulfide linkage or NHS-PEO(4)-Maleimide as a cross linker. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Low Mw chitosan [14], [15] and its modifications [16], [17] have been successfully used for transfection of both DNA and siRNA [18]. This was supported by our previous study of low Mw chitosan of 16 kDa, which showed the potential for transfection in vitro [19]. One problem of chitosan-DNA nanoparticles that formed from low Mw chitosan has been the aggregation of the particles [20] before transfection, which enlarges the complexes’ size and may interfere with the transfection.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…Low Mw chitosan [14], [15] and its modifications [16], [17] have been successfully used for transfection of both DNA and siRNA [18]. This was supported by our previous study of low Mw chitosan of 16 kDa, which showed the potential for transfection in vitro [19]. One problem of chitosan-DNA nanoparticles that formed from low Mw chitosan has been the aggregation of the particles [20] before transfection, which enlarges the complexes’ size and may interfere with the transfection.…”
Section: Introductionmentioning
confidence: 77%
“…It was the product of depolymerization reaction of the commercial chitosan (Mw ∼470 kDa, DDA ∼80%) with sodium nitrite. [19], [26]. Briefly, 2 g of chitosan was dissolved in 100 mL of acetic acid (6% v/v) under magnetic stirring at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…But the study of Supaprutsahul et al (2010) revealed much higher transfection efficiency with the depolymerised chitosan at Mw ~16 kDa (or Mn ~ 6.5). This may be because of the different chitosan/DNA ratio, as the previous study used low N/P ratio, while Supaprutsakul et al (2010) used chitosan/plasmid at an N/P ratio of about 56:1, which meant than a much higher amount of chitosan was used for the lower Mw. This was consistent with the study of Romøren et al (2003), who found that low Mw chitosan was beneficial at the higher charge ratio of the complexes.…”
Section: Molecular Weight (Mw)mentioning
confidence: 96%
“…Some studies have reported of high transfection efficiency with high Mw chitosan (Huang et al, 2005;Kiang et al, 2004;MacLaughlin et al, 1998). Other studies have reported that low Mw chitosan has better transfection efficiency (Koping-Hoggard et al, 2004;Lavertu et al, 2006;Supaprutsakul et al, 2010). MacLaughlin et.al.…”
Section: Molecular Weight (Mw)mentioning
confidence: 99%
“…Epidermal growth factor (EGF) can bind with receptors of tumor cells with high affinity; therefore, Supaprutsakul et al recently conjugated EGF to chitosan for tumor-targeted gene delivery [56]. However, compared with chitosan/DNA complexes, EGF-conjugated chitosan/DNA complexes did not improve transfection efficiency due to aggregation of the complexes.…”
Section: Epidermal Growth Factor and Rgdmentioning
confidence: 99%